"Quality Leadership Matters": A Research-Based Survey of Graduate Programming. (June 2018) - Mullen, Carol A.; Eadens, Daniel W.
This empirical study contributes to the dialogue about quality leadership and national trends involving standards-based program review. It is the first to utilize the 2016 Council for the Accreditation of Educator Preparation (CAEP) Standards for graduate programs and separately from accreditation and sponsorship. The literature on quality leadership is reviewed, and results from an original instrument are described. Survey influences included leadership literature, the CAEP Standards, and the University Council for Educational Administration's artifacts. Students and completers' feedback was on program effectiveness, satisfaction, impact, and ethics. Variance was found in perceptions of quality, relevance, and learning. Contradictory beliefs of program effectiveness can stimulate discussion and strengthen programming.